Dipstick urine analysis screening among asymptomatic school children - Hajar, Farah (Medknow Publications & Media Pvt Ltd, 2011)
BACKGROUND: Mass urinary screening is a useful tool to identify children with asymptomatic progressive renal diseases. A dipstick urinalysis screening was conducted to detect such prevalence and to set up a more effective screening program for children. PATIENTS AND METHODS: A cross sectional study was carried out in seven nurseries and primary schools in different regions of Lebanon (Beirut, North Lebanon, and Valley of Bekaa) between February 2010 and March 2010. Eight hundred seventy asymptomatic children were enrolled in this study. First morning mid steam urine samples were obtained from students and were tested by dipstick method. Children with abnormal findings were re-tested after fifteen days. RESULTS: Twenty five (2.9%) children had urinary abnormalities at the first screening; Eighteen (72%) of them still had abnormal results at the second screening. Among all the students, hematuria was the most common abnormality found with a prevalence of 1.5%, followed by nitrituria (0.45%), combined hematuria and nitrituria (0.45%) and proteinuria (0.1%). Urinary abnormalities were more common in females than in males. With respect to age, most positive results were detected at 6 years of age. Hematuria and proteinuria were mainly present in the North of Lebanon. CONCLUSION: Asymptomatic urinary abnormalities might be detected by urine screening program at school age. Further work-up should be offered to define the exact etiology of any abnormal finding and to determine whether early detection of renal disorders in childhood will lead to effective interventions and reduction in the number of individuals who develop end-stage renal disease.